PENERAPAN KOMUNIKASI RISIKO BENCANA PADA THE CANGKRINGAN JOGJA VILLAS & SPA - Sherly Hindra Negoro (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Natural disaster are one the form of crisis that comes from external organization. Natural disaster are unpredictable. For organization, risk communication is important as part of prevention or need anticipation effort. This research discusses risk communication in the context of disaster that implemented by hotels located in high risk disaster area especially Merapi eruption. Disaster areas can be a tourist attraction. On the other hand, the natural disaster can also decrease the number of tourist visit. This research is a qualitative research with case study method. The results showed that The Cangkringan Jogja Villas Spa carries out risk identification and analysis to prevent a bad situation for the public. Risk analysis is carried out with knowledge approach and cultural approach. The Cangkringan Jogja Villas Spa involves internal and external parties to communicate risk. In order to anticipate ambiguous information, The Cangkringan Jogja Villas Spa formed an Emergency Response Unit. They are responsible for carrying out the functions and roles based on Standard Operating Procedure (SOP).